Practical training report: Kuala Krai Land and District Office / Muhammad ‘Izzat Bahauddin Zulkipli - Zulkipli, Muhammad ‘Izzat Bahauddin (University Technology MARA Sarawak, 2018)
Kuala Krai is the second largest district in the state after Gua Musang. This district is one of the oldest district that were established by the British in 1909. However, Kuala Krai was officially recognized on September 1, 1977 where before it was known Jajahan Ulu Kelantan which includes all of Gua Musang and Kuala Balah in the Jajahan Jeli. The District Administrative Center was initially located in Kg. Mengkebang, Jalan Batu Lada and then moved near Tangga Krai (Tangga Bradley) in 1927. Currently, the District Administration has moved to a new building in the center of Guchil on 22 April 1985.